2021
DOI: 10.1088/1742-6596/1988/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Prediction Using ARIMA, Neural Network and LSTM Models

Abstract: Since the past decades, prediction of stock price has been an important and challenging task to yield the most significant profit for a company. In the era of big data, predicting the stock price using machine learning has become popular among the financial analysts since the accuracy of the prediction can be improved using these techniques. In this paper, auto-regressive integrated moving average (ARIMA), neural network (NN) and long short-term memory network (LSTM) have been used to predict Bursa Malaysia’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The authors demonstrated that hybrid models achieve better performance than a single model for stock market predictions. In Ho et al (1988), a hybrid method of ARIMA with a neural network and long short-term memory (LSTM) network was applied to predict the Bursa Malaysia stock exchange during the COVID-19 pandemic period.…”
Section: Methodsmentioning
confidence: 99%
“…The authors demonstrated that hybrid models achieve better performance than a single model for stock market predictions. In Ho et al (1988), a hybrid method of ARIMA with a neural network and long short-term memory (LSTM) network was applied to predict the Bursa Malaysia stock exchange during the COVID-19 pandemic period.…”
Section: Methodsmentioning
confidence: 99%
“…Many scholars have applied ARIMA and LSTM to analyze FinTech companies. ARIMA and LSTM models have great potential in financial technology stock analysis, and combining multiple data sources and technologies can improve prediction accuracy [9]. Some scholars combine ARIMA and LSTM to predict the future market value of FinTech companies in the United States, and incorporate data preprocessing techniques such as differentiation, normalization, and normalization to improve the accuracy of predictions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several deep learning-based regression models were built using LSTM networks, and we found that the LSTMbased univariate model, which uses data from a previous week as input for predictions, provides the most accurate result. [1] [2] Additionally, in [5], A hybrid of RNN and LSTM is constructed to make prediction of the stock price trend. Their comparison between the percentage of accuracy of both ARIMA and LSTM used on series data manifested that LSTM outperforms ARIMA.…”
Section: Related Researchmentioning
confidence: 99%